Program Pojok Baca Untuk Meningkatkan Kemampuan Literasi dan Numerasi Siswa Sekolah Dasar di Desa - Darmadi; Cicilia Novi Primiani; Sudarmiani; Pujiati; Sanusi (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Student learning in rural elementary schools during the Covid-19 pandemic has an impact on learning motivation. Learning activities in Purworejo Village, Pilangkenceng, Madiun Regency during the Covid-19 Pandemic experienced obstacles. Learning using information technology cannot run optimally. Many elementary school students lack motivation in reading and arithmetic. The purpose of service activities is to improve student literacy and numeracy through the reading corner program. The target of this service activity is elementary school students in Purworejo Village, Kacan Pilangkenceng, Madiun Regency. The service method is carried out with assistance, including survey activity procedures, socialization, training, learning, and evaluation. The results of the implementation of the